Safety and efficacy of low dose Escherichia coli enterotoxin adjuvant for urease based oral immunisation against Helicobacter pylori in healthy volunteers. Issue 5 (1st November 2002) - Banerjee, S; Medina-Fatimi, A; Nichols, R; Tendler, D; Michetti, M; Simon, J; Kelly, C P; Monath, T P; Michetti, P
Abstract : Background and aims: Escherichia coli heat labile enterotoxin (LT) at doses of 5 μg or 10 μg has adjuvant activity for oral immunisation in humans infected with Helicobacter pylori, but causes severe diarrhoea. This study was undertaken to establish a safe and effective dose of LT, to confirm the safety of recombinant urease, and to compare the immunogenicity of orally compared with enterically delivered urease. Methods: 42 healthy adults without present or past H pylori infection were randomised to receive 60 mg recombinant H pylori urease in soluble or in encapsulated form, given with doses of LT ranging from 0 μg to 2.5 μg. Four oral doses were administered at day 1, 8, 29, and 57. Specific IgG, IgA, and antibody secreting cells were measured as well as total α4β7 integrin positive lymphocyte responses. Results: Enterically delivered urease was well tolerated and no serious adverse events occurred. Mild diarrhoea (one to four loose stools) occurred after the first immunisation in 50% (6 of 12) of the volunteers exposed to 2.5 μg LT (p=0.06; paired t test, compared with baseline) but not in volunteers exposed to lower LT doses. Immune responses occurred in five (p=0.048; Fisher's exact test), one, two, and one of six subjects exposed to 2.5 μg, 0.5 μg, 0.1 μg, and no LT, respectively. Significant CD4 +, CD69 +, and CD45RO hi responses occurred over time among α4β7 hi lymphocytes in volunteers receiving 2.5 μg LT. Enterically delivered urease induced higher lymphocyte responses than soluble urease. Conclusions: The safety of H pylori urease is confirmed. Oral LT may conserve its adjuvant activity at low doses with minimal side effects.